Prognostic impact of ventral versus dorsal tumor location after total mesorectal excision of rectal cancer - Franz, Clemens; Lang, Hans M.; Ghamarnejad, Omid; Khajeh, Elias; Mehrabi, Arianeb; Ulrich, Alexis; Schneider, Martin; Büchler, Markus W.; Kulu, Yakup (Annals of surgical oncology, 2020)
Multidisciplinary treatment of rectal cancer, including neoadjuvant treatment, total mesorectal excision, and adjuvant chemotherapy, have improved oncological outcome. Preoperative radiation therapy is advocated by national and international guidelines in all patients with AJCC stage II and III rectal cancer. Although this treatment reduces local recurrence rates with no effect on overall survival, there are possible short- and long-term side effects of radiation exposure, so patients should be carefully selected for neoadjuvant radiation therapy.
Published Online: 23 September 2019
Gesehen am 07.05.2020